Pseudomonas luteola cutaneous abscess and bacteraemia in a previously healthy man. - Dalamaga, Maria; Karmaniolas, Konstantinos; Chavelas, Charilaos; Liatis, Stavros; Matekovits, Helen; Migdalis, Ilias (Scand J Infect Dis, 2004)
Pseudomonas luteola is uncommonly implicated in clinical infections, but it constitutes a significant nosocomial pathogen causing mainly infections associated with foreign material. This report describes an unusual case of a Pseudomonas luteola strain that infected and caused cutaneous abscess and bacteraemia in a previously healthy man.
Keywords: Abscess; Aged; Bacteremia; Humans; Male; Pseudomonas; Pseudomonas Infections; Skin Diseases, Bacterial